Growth and location of bacterial colonies within dairy foods using microscopy techniques: a review - Hickey, Cian D.; Sheehan, Jeremiah J.; Wilkinson, Martin G.; Auty, Mark A. E. (Frontiers in Microbiology, 2015)
The growth, location and distribution of bacterial colonies in dairy products are important factors for the ripening and flavor development of cheeses, yogurts and soured creams. Starter, non-starter, spoilage and pathogenic bacteria all become entrapped in the developing casein matrix of dairy foods. In order to visualize these bacterial colonies and the environments surrounding them, microscopy techniques are used. The use of various microscopy methods allow for the rapid detection, enumeration and distribution of starter, non-starter and pathogenic bacteria in dairy foods. Confocal laser scanning microscopy is extensively utilised to identify bacteria location via the use of fluorescent dyes. Further study is needed in relation to the development of micro- gradients and localized ripening parameters in dairy products due to the location of bacteria at the protein-fat interface. Development in the area of bacterial discrimination using microscopy techniques and fluorescent dyes/tags is needed as the benefits of rapidly identifying spoilage/pathogenic bacteria early in product manufacture would be of huge benefit in relation to both safety and financial concerns.